« Enseigner avec la science-fiction » : quelques jalons pour une histoire récente de l’enseignement de la science-fiction en France (1970-2020) - Philippe Clermont (ReS Futurae)
The aim of this article is to provide some answers to the question of the use and content of science fiction (SF) in the teaching of literature, from the historical perspective of French secondary education. It shows that SF – since the 1970s – has been a constant subject of teaching in French secondary schools, first approached in a marginal way, then taking on a greater role – particularly in school textbooks – as curricula changed and children’s literature was introduced into the school corpus (1980s). The time milestones selected enable us to identify the main trends according to periods corresponding to developments initiated either by research or by official national education programs. An analysis of examples shows that, from the 1970s, SF was regularly the subject of pedagogical and didactic proposals. In a first approach, the examples selected are each time situated at the junction of applied university research and analyzed classroom experiences. A second section analyzes the use of SF in a panel of textbooks at the turn of the millennium. The third part of the study offers reflections on more contemporary teaching. The constant presence of SF in French language teaching is nonetheless minor, whatever the period considered.